Optimization of Islamic Law in its Role to Prevent Covid-19 - Hafiz Rafi Uddin; Natal Kristono; Fahrihan Nur Adria (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to explain the importance of maintaining religious moderation amid the COVID-19 pandemic. The approach used is socio-religious by looking at news facts that happen to residents. result of sharing understanding that moderate priority on religion during the covid 19 pandemic is a must. For this reason, the public is trying to understand more about maintaining their own safety and participating in protecting and assisting the government in dealing with the Covid-19 virus. The main focus of the war that occurred during the Covid-19 Pandemic for Muslims was the maintenance of religion, meaning that worship activities under any circumstances must be carried out. So Islamic law is always present in every situation, so that Muslims remain calm in carrying out their religious activities. with various kinds of health references about the dangers of Covid-19 and maintaining the security and stability of the country.